Assessment of Factors Influencing Utilization of Maternal and Child Health Services in The Federal Capital Territory (FCT), Abuja, Nigeria - Oguntimehin, F. B.; Usar, I. J. (British Journal of Healthcare and Medical Research, 2023)
Background: Although Nigeria has made progress in attaining the third sustainable development goal, maternal and child mortality remains a challenge to attaining universal health coverage. Utilization of maternal and child health services (MCH) is not uniform in the country, with the southern region outperforming the northern region, and within the northern region, the north central is outperforming the North West and east. Even in the north central, majority of state lag behind the federal capital territory (FCT), Abuja, in the uptake of MCH services. This study aimed to understand the determinants of maternal and child health service uptake in FCT. The evidence generated should help expand MCH services delivery in the FCT and other similar settings in Nigeria and beyond. Methodology: The research adopted a cross-sectional, mixed methods design in Bwari and Kuje Area Councils of Abuja, using a synthesis of the Ensor and Cooper demand and supply paradigm of health service uptake and the Andersen and Newman Behavioural Model for health service utilization. Qualitative data was obtained through Key Informant Interviews, In-Depth Interviews, and Focus group discussions with parents of under-five year children, pregnant women, health workers, program managers and community leaders. Quantitative data was collected through a household survey of women of childbearing age, using modified WHO Health Access and Use household survey questionnaire. Thematic analysis of the qualitative data was done to determine patterns relevant study objectives using Dedoose software. Quantitative analysis involved univariate descriptive analysis of respondents’ socio-demographics and multivariate logistic regression to determine the predictive value and relative importance of the predisposing, enabling, and needs determinants of MCH uptake. Result: Factors that favoured the uptake of MCH services included service availability, affordable cost of care, accessibility and proximity of health facilities, and perceived good knowledge and capacity of health workers. No religious or cultural barrier to MCH service uptake was reported. Education and employment status were statistically significant determinants of ANC uptake. Religion, level of education, and employment were statistically significant predisposing determinants of having skilled birth attendance (SBA). Also, employment and educational status were statistically significant predisposing factors of immunization uptake. Financial barriers, poor knowledge of availability services, previous negative experience with service utilization, poor perception on the value of MCH services were factors limiting uptake of MCH services. Conclusion: The study concludes that both demand and supply determinants of MCH services utilization were functionally demonstrated in the study area. However, the lack of health insurance scheme is a key limitation for universal coverage of MCH services in the study area. We recommend continuous improvement in health facility infrastructure and human resources capacity building by public authorities, to sustain and improve the current level of MCHs services delivery in the area. Furthermore, government should scale up the roll out of its national health insurance scheme to cover more enrollees.